The Band Effect—Physically Strenuous Music Making Increases Esthetic Appreciation of Music - Fritz, Thomas H.; Schneider, Lydia; Villringer, Arno (Frontiers in Neuroscience, 2016)
The aesthetic appreciation of music is strongly influenced by cultural background and personal taste. One would expect that this would complicate the utilizability of musical feedback in paradigms, such that music would only be perceived as a reward if it complies to personal aesthetic appreciation. Here we report data where we assessed aesthetic appreciation of music after 1. a physically strenuous music improvisation and 2. after passive music listening (where participants aesthetically assessed similar music). Data are reported from two experiments where different patient groups performed Jymmin, a music feedback method where exercise equipment is modified in such a way that it can be played like musical instruments by modulating musical parameters in a composition software. This combines physical exertion with musical performance in a fashion that has previously been shown to have a number of positive psychological effects such as enhanced mood and reduced perceived exertion. In both experiments aesthetic appreciation of musical presentations during Jymmin and a control condition without musical agency were compared. Data show that both patient groups perceived the musical outcome of their own performance as more aesthetically pleasing than similar music they listened to passively. This suggests that the act of making music (when combined with physical exertion) is associated with a positivity bias about the perceived aesthetical quality of the musical outcome. The outcome of personal musical agency thus tends to be perceived as rewarding even if it does not comply with personal aesthetic appreciation. This suggests that musical feedback interventions may not always have to be highly individualized because individual taste may not always be crucial. The results also suggest that the method applied here may be efficient at encouraging music listeners to actively explore new musical styles that they might otherwise be reluctant to listen to (e.g. avant-garde music). The results also hint towards a deeper understanding of why musicians, who exert themselves physically during musical performances to generate music and, regardless of the type of music they are playing, typically find the physically-demanding experience aesthetically satisfying.